THE PARENTAL RESPONSIBILITY CONCEPT IN REPLACING CRIMINAL RESPONSIBILITY OF CHILD TO PARENT (THE STUDY OF INDONESIAN TRIBES CULTURE IN LAMPUNG AND AGA BALINESE TRIBES) - Umi Rozah (Fakultas Hukum, Universitas Diponegoro, 2017)
Crime is some action which declared that it should not be done by anyone, no matters adults, juveniles or child. Anyone should be punished if he/she has done any crime which harmed or injuried someone or violated social order, as that was formulated in an Act and threated by punishment. An interesting question here are : How is the roles of parents in liability for any crimes which done by her/his child? Why the parents should endure liabilities for any crime that he/she did not do it but just for child that may be they know nothing about that.This written based on research which is performed in Lampung Tribe Society and Balinese Tribe Society. Law is a mirror of society become an entry poin to access and to understand how cultures both of Lampung and Balinese Tribes Society to solve any crime that was done by the child . Here, the author wrote based on the penal codes Cepalo Walu Ngepuluh which is prevailing in Lampung Tribes Culture and Kitab Manawa Dharmacastra which is applying at Balinese Tribes Culture.This method research was performed by sociol legal research approach, that mixed socio research approach to search values of both tribes society behavior in resolve the matters or crimes which was done by juveniles in the one hand, and in the other hand this research used libraries approach to search any documents or any literatures that be related with how to resolve any crime was done by a juvenile.This article is very interesting because in Indonesian Penal Codes did not impose parental responsibility for the child’s offence . So this article could be the way out to relocating the child’s criminal responsibility to his/her parents.